2018
DOI: 10.3390/ijms19020375
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone (GH) and Gonadotropin-Releasing Hormone (GnRH) in the Central Nervous System: A Potential Neurological Combinatory Therapy?

Abstract: This brief review of the neurological effects of growth hormone (GH) and gonadotropin-releasing hormone (GnRH) in the brain, particularly in the cerebral cortex, hypothalamus, hippocampus, cerebellum, spinal cord, neural retina, and brain tumors, summarizes recent information about their therapeutic potential as treatments for different neuropathologies and neurodegenerative processes. The effect of GH and GnRH (by independent administration) has been associated with beneficial impacts in patients with brain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 193 publications
(233 reference statements)
2
27
0
Order By: Relevance
“…Growth hormone (GH) is a mitogenic peptide synthetized and released by somatotrophic cells in the pituitary gland. In addition, GH can be synthetized and released by neurons within the CNS, where it participates in stress-response and neuroprotection ( Martínez-Moreno et al, 2018 ). In the human retina, GH and GH receptors (GHR) are expressed in RGCs, where the existence of RGC autocrine regulation by GH has been hypothesized ( Sanders et al, 2006 , 2009 ; Harvey et al, 2009 ).…”
Section: Neurotrophic/growth Factors (Neuronal Vascular or Both)mentioning
confidence: 99%
“…Growth hormone (GH) is a mitogenic peptide synthetized and released by somatotrophic cells in the pituitary gland. In addition, GH can be synthetized and released by neurons within the CNS, where it participates in stress-response and neuroprotection ( Martínez-Moreno et al, 2018 ). In the human retina, GH and GH receptors (GHR) are expressed in RGCs, where the existence of RGC autocrine regulation by GH has been hypothesized ( Sanders et al, 2006 , 2009 ; Harvey et al, 2009 ).…”
Section: Neurotrophic/growth Factors (Neuronal Vascular or Both)mentioning
confidence: 99%
“…1,2 Regarding the neural effects of GH, it has been shown recently that its clinical application has revealed promising results as a treatment for stroke, spinal cord injury, brain trauma, and neurodegenerative diseases. 3,4 Also, important neurotrophic actions of GH in the neuroretina are related with the modulation of developmental apoptosis and neuroprotection, 5,6 because it has been observed that exogenous GH administration protects against experimental excitotoxic damage. 7,8 In addition, GH acts during neural differentiation and network establishment to promote axon growth 9,10 and synaptogenesis.…”
mentioning
confidence: 99%
“…It is well known that there are two different steps of GH action: at first, GH is directly mediated by GHR to be transducted to IGF1; and then the IGF-1 acts on target cells to exert the physiological effect of GH [ 4 , 81 ]. Although GH acts in nearly every tissue of the body, the most known for its growth promoting effect of GH is on cartilage and bone, especially during the adolescent years.…”
Section: Discussionmentioning
confidence: 99%
“…Growth hormone (GH), also known as somatotropin, is a peptide hormone released from the anterior pituitary somatotroph cells. GH is involved in the promotion of growth, cell division and regeneration [ 1 , 2 ], the regulation of metabolism, immune, reproductive, and cardiovascular systems, and the brain [ 3 , 4 ]. GH effects are directly mediated through the GH receptor (GHR) and indirectly via insulin-like growth factor 1 (IGF-1).…”
Section: Introductionmentioning
confidence: 99%